The Application of Pinch Technology Heat Exchanger Network Analysis at a Crude Oil Refinery - Crisostomo, E.V.; Wood, R.M. (Philippine Engineering Journal; Vol 9 No 2 (1988), 2021)
This paper applies the principles of pinch technology to data obtained from a crude oil refinery. The existing design is highly integrated and additional heat exchange surface had been added following the increase in oil prices in the last decade. However, the targeting procedures identified possibilities for energy savings and a retrofit saving about 10% of the existing energy consumption with about a two-year payback is proposed.